The Impact of Automotive Engineering Students’ Understanding of Renewable Energy (Hybrid Energy Conversion) - Fajar Maulana; Ustafiano, Bintha (Universitas Lancang Kuning, 2025)
This study investigates the understanding of Automotive Engineering students regarding renewable energy, particularly focusing on hybrid energy conversion. The rapid advancement of renewable energy technologies, including electric, hybrid, and hydrogen-powered vehicles, has made it essential for automotive engineering students to acquire knowledge about these energy sources. The main objective of this research is to assess the comprehension level of students about renewable energy and hybrid energy conversion, a key component of modern automotive systems. Data were collected through questionnaires, semi-structured interviews, and classroom observations involving 60 students and 5 teachers. The findings indicate that while 65% of students possess a basic understanding of renewable energy sources such as solar, wind, and hydro, only 40% can accurately describe hybrid energy conversion mechanisms. The results suggest that laboratory-based learning and industry exposure significantly enhance student comprehension. This research highlights the importance of integrating hybrid energy concepts into the curriculum to prepare students for the evolving demands of the automotive industry and contribute to the global transition towards sustainable energy.